irawaddy吧 关注:390贴子:47,066
$\left(\begin{array}{ccc}
V_{11} & V_{12} & \cdots \\
V_{21} & V_{22} & \cdots \\
\vdots & \vdots & \ddots
\end{array}\right) \left(\begin{array}{c}
\langle 1^{(0)}|l^{(0)}\rangle \\
\langle 2^{(0)}|l^{(0)}\rangle \\
\vdots
\end{array}\right) = \Delta_l^{(1)} \left(\begin{array}{c}
\langle 1^{(0)}|l^{(0)}\rangle \\
\langle 2^{(0)}|l^{(0)}\rangle \\
\vdots
\end{array}\right)$


IP属地:北京1楼2014-11-22 12:30回复
    $V=\begin{array}{cccc}
    2s & 2p\quad m=0 & 2p\quad m=1 & 2p\quad m=-1 \\
    \left(0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
    \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
    0 & 0 & 0 & 0 \\
    0 & 0 & 0 & 0
    \right)
    \end{array}$


    IP属地:北京4楼2014-11-24 14:59
    回复
      $V=\begin{array}{cccc}
      2s & 2p\quad m=0 & 2p\quad m=1 & 2p\quad m=-1 \\
      \left(0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
      \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
      0 & 0 & 0 & 0 \\
      0 & 0 & 0 & 0 \right)
      \end{array}$


      IP属地:北京5楼2014-11-24 15:00
      回复
        $V=\begin{array}{cccc}
        2s & 2p\quad m=0 & 2p\quad m=1 & 2p\quad m=-1 \\
        0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
        \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
        0 & 0 & 0 & 0 \\
        0 & 0 & 0 & 0
        \end{array}$


        IP属地:北京6楼2014-11-24 15:01
        回复
          $V=\begin{array}{cccc}
          \left(0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
          \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
          0 & 0 & 0 & 0 \\
          0 & 0 & 0 & 0
          \right)\end{array}$


          IP属地:北京7楼2014-11-24 15:02
          回复
            V=\begin{array}{cccc}
            2s & 2p\quad m=0 & 2p\quad m=1 & 2p\quad m=-1 \\
            \left{begin{array}{cccc} 0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
            \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
            0 & 0 & 0 & 0 \\
            0 & 0 & 0 & 0
            \end{array}\right)\end{array}


            IP属地:北京8楼2014-11-24 15:03
            回复
              $V=\left(\begin{array}{cccc}
              0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
              \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
              0 & 0 & 0 & 0 \\
              0 & 0 & 0 & 0
              right)\end{array}$


              IP属地:北京9楼2014-11-24 15:04
              回复
                V=\left(\begin{array}{cccc}
                0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
                \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
                0 & 0 & 0 & 0 \\
                0 & 0 & 0 & 0
                \end{array}\right)


                IP属地:北京10楼2014-11-24 15:05
                回复
                  $V=\left(\begin{array}{cccc}
                  0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
                  \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
                  0 & 0 & 0 & 0 \\
                  0 & 0 & 0 & 0
                  \end{array}\right)$


                  IP属地:北京11楼2014-11-24 15:05
                  回复
                    $V=\left(\begin{array}{cccc}
                    0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
                    \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
                    0 & 0 & \phantom{\langle 2s|V|2}0\phantom{,m=0} & 0 \\
                    0 & 0 & 0 & \phantom{\langle 2s|V|2}0\phantom{,m=0}
                    \end{array}\right)$


                    IP属地:北京12楼2014-11-24 15:07
                    回复
                      $\phantom{V=(\langle 2p,m)}2s\phantom{|V|2s\rangle\quad\langle 2s|}2p\quad m=0\phantom{0\rangle\qquad}2p\quad m=0\phantom{\quad}2p\quad m=-1
                      V=\left(\begin{array}{cccc}
                      0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
                      \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
                      0 & 0 & \phantom{\langle 2s|V|2}0\phantom{,m=0} & 0 \\
                      0 & 0 & 0 & \phantom{\langle 2s|V|2}0\phantom{,m=0}
                      \end{array}\right)$


                      IP属地:北京13楼2014-11-24 15:10
                      回复
                        $\phantom{V=(\langle 2p,m)}2s\phantom{|V|2s\rangle\quad\langle 2s|}2p\quad m=0\phantom{0\rangle\qquad}2p\quad m=0\phantom{\quad}2p\quad m=-1 \\
                        V=\left(\begin{array}{cccc}
                        0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
                        \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
                        0 & 0 & \phantom{\langle 2s|V|2}0\phantom{,m=0} & 0 \\
                        0 & 0 & 0 & \phantom{\langle 2s|V|2}0\phantom{,m=0}
                        \end{array}\right)$


                        IP属地:北京14楼2014-11-24 15:11
                        回复
                          $\phantom{V=(\langle 2p,m)\qquad}2s\phantom{|V|2s\rangle\quad\langle 2s|}2p\quad m=0\phantom{0\rangle\qquad}2p\quad m=0\phantom{\quad}2p\quad m=-1 \\
                          V=\left(\begin{array}{cccc}
                          0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
                          \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
                          0 & 0 & \phantom{\langle 2s|V|2}0\phantom{,m=0} & 0 \\
                          0 & 0 & 0 & \phantom{\langle 2s|V|2}0\phantom{,m=0}
                          \end{array}\right)$


                          IP属地:北京15楼2014-11-24 15:11
                          回复
                            $
                            \phantom{V=(\langle 2p,m)\quad}2s\phantom{|V|2s\rangle\quad\langle 2s|}2p\quad m=0\phantom{0\rangle\qquad}2p\quad m=0\phantom{\quad}2p\quad m=-1 \\
                            V=\left(\begin{array}{cccc}
                            0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
                            \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
                            0 & 0 & \phantom{\langle 2s|V|2}0\phantom{,m=0} & 0 \\
                            0 & 0 & 0 & \phantom{\langle 2s|V|2}0\phantom{,m=0}
                            \end{array}\right)
                            $


                            IP属地:北京16楼2014-11-24 15:12
                            回复
                              $
                              \phantom{V=(\langle 2p,m)\quad}2s\phantom{|V|2s\rangle\quad\langle 2s|\quad}2p\quad m=0\phantom{0\rangle\qquad}2p\quad m=0\phantom{\quad}2p\quad m=-1 \\
                              V=\left(\begin{array}{cccc}
                              0 & \langle 2s|V|2p,m=0\rangle & 0 & 0 \\
                              \langle 2p,m=0|V|2s\rangle & 0 & 0 & 0 \\
                              0 & 0 & \phantom{\langle 2s|V|2}0\phantom{,m=0} & 0 \\
                              0 & 0 & 0 & \phantom{\langle 2s|V|2}0\phantom{,m=0}
                              \end{array}\right)
                              $


                              IP属地:北京17楼2014-11-24 15:13
                              回复